Iron-rich Kupffer cells exhibit phenotypic changes during the development of liver fibrosis in NASH - Kanamori, Yohei (iScience, 2021)
Although recent evidence suggests the involvement of iron accumulation in the pathogenesis of nonalcoholic steatohepatitis (NASH), the underlying mechanisms remain poorly understood. Previously, we reported a unique histological structure termed “crown-like structure (CLS),” where liver-resident macrophages (Kupffer cells) surround dead hepatocytes, scavenge their debris, and induce inflammation and fibrosis in NASH. In this study, using magnetic column separation, we show that iron-rich Kupffer cells exhibit proinflammatory and profibrotic phenotypic changes during the development of NASH, at least partly, through activation of MiT/TFE transcription factors. Activation of MiT/TFE transcription factors is observed in Kupffer cells forming CLSs in murine and human NASH. Iron chelation effectively attenuates liver fibrosis in a murine NASH model. This study provides insight into the pathophysiologic role of iron in NASH. Our data also shed light on a unique macrophage subset rich in iron that contributes to CLS formation and serves as a driver of liver fibrosis.